Surgical Management of Ulcerative Colitis in the Era of Biologicals. Issue 1 (January 2015) - Devaraj, Bikash; Kaiser, Andreas M.
Abstract : Purpose: Proctocolectomy has been a curative option for patients with severe ulcerative colitis. In recent years, there has been a growing use of medical salvage therapy in the management of patients with moderate to severe ulcerative colitis. We aimed at reviewing the role of surgical management in a time of intensified medical management on the basis of published trial data. The aim was to determine the efficacy of aggressive medical versus surgical management in achieving multifaceted treatment goals. Methods: A comprehensive search of Pubmed, Medline, the Cochrane database was performed. Abstracts were evaluated for relevance. Selected articles were then reviewed in detail, including references. Recommendations were then drafted based on evidence and conclusions in the selected articles. Results: The majority of patients with UC will not need surgery. However, steroid-refractoriness and steroid-dependence signal a subset of patients with more challenging disease. Biological therapy has been shown to achieve short-term improvement and temporarily reduce the need for a colectomy. However, there is a substantial financial and medical price to pay because a high fraction of these salvaged patients will still need a curative colectomy but may be exposed to the negative impact of prolonged immunosuppression, chronic illness, and a higher probability to require 3 rather than 2 operations. Proctocolectomy with ileo-anal pouch anastomosis—performed in 1, 2, or 3 steps depending on the patient's condition—remains the surgical procedure of choice. Even though it has its share of possible complications, it has been associated with excellent long-term outcomes and high levels of satisfaction, such that in the majority of patients they become indistinguishable from unaffected normal individuals. Conclusions: The current data demonstrate that use of medical salvage therapy in the treatment of UC will likely continue to grow and evolve. Consensus is being developed to better define and predict failure of medical therapy and clarify the role of the different treatment modalities. For many patients, sacrificing the nonresponsive diseased colon is an underused or unnecessarily delayed chance to normalize their health and life. Biologicals in many instances may have to be considered the bridge to that end. Abstract : Article first published online 16 September 2014